2015
DOI: 10.1039/c5ra16670e
|View full text |Cite
|
Sign up to set email alerts
|

Role of the coupler to design organic magnetic molecules: LUMO plays an important role in magnetic exchange

Abstract: The occupation number and spatial position of the LUMO play an important role in magnetic exchange in diradicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 54 publications
8
53
0
Order By: Relevance
“…In couple of our recent works, we have studied that the SOMO-SOMO gap is not responsible for the strength of magnetic coupling, rather HOMO-LUMO gap plays a more important role. 39,45,46 If we focus on the energy difference between HOMO and LUMO in this study, it has been found that on going from diradical based allene to its higher homologue ( [5]-and [7]-cumulene) in each series, there is a smooth decrease in HOMO-LUMO energy gap. Hermann et.…”
Section: Mechanism Of Magnetic Interactionmentioning
confidence: 97%
“…In couple of our recent works, we have studied that the SOMO-SOMO gap is not responsible for the strength of magnetic coupling, rather HOMO-LUMO gap plays a more important role. 39,45,46 If we focus on the energy difference between HOMO and LUMO in this study, it has been found that on going from diradical based allene to its higher homologue ( [5]-and [7]-cumulene) in each series, there is a smooth decrease in HOMO-LUMO energy gap. Hermann et.…”
Section: Mechanism Of Magnetic Interactionmentioning
confidence: 97%
“…Thus, the HOMO and LUMO still are popularly utilized to analyze the electronic structures, electronic properties and chemical reactivity of the molecules and chemical systems. On the other hand, although Shil et al . reported that LUMO plays an important role in magnetic exchange, we find that LUMO and other unoccupied orbitals of the bridge would play less roles than its HOMO because HOMOs of the radical groups actually are SOMOs with the LUMO properties and their energy matchings with the bridge HOMO favor the spin coupling interaction between two radical groups through the bridge.…”
Section: Resultsmentioning
confidence: 99%
“…This also confirms the role of LUMO in the magnetic exchange coupling. [64] This might be linked to the fact that the LUMO spans over the entire molecule, whereas the SOMOs are located on the radical units.…”
Section: Molecular Orbitalsmentioning
confidence: 99%